ЭКОЛОГИЯЛЫҚ АУДИТ – ТАБИҒИ БАЙЛЫҚТАРДЫ ПАЙДАЛАНУДЫ БАСҚАРУДЫҢ ЭКОНОМИКАЛЫҚ ҚҰРАЛЫ - Оңдаш, А О (Journal of Economic Research & Business Administration, 2015)
Ecological auditing-independent research of all aspects of economic activities of the industrial enterprise of any pattern of ownership for an establishment of the size of direct or indirect influence on a condition of an environment. Its purpose - reduction of nature protection activity conformity with requirements of the legislation and statutory acts,optimization of use of natural resources, decrease and ordering energy-consumption, reduction of waste, prevention of emergency dumps, emissions and technogenic accidents.